A Review of the AAOS International Scholars Program after 14 Years: Professional Development and Education of the Recipients - Gurevich, Anna; Sabharwal, Sanjeev; Christian, Matthew W.; Stetson, William B.; Spiegel, David A. (Frontiers in Education, 2017)
Introduction The AAOS International Scholars Program was launched in 2002 with the goal of enhancing the knowledge and skills of orthopedic surgeons in underserved regions. The goals of this study were to (1) characterize the professional and practice profile of scholarship recipients, (2) assess the perceived impact of this short-term educational experience on their clinical practice, (3) if/how the knowledge and skills have been disseminated to students and/or colleagues, and (4) assess career development in a subset of scholarship recipients. Method The AAOS international scholar database was accessed to review the scholarship applications and all available follow-up questionnaires for 103 scholarship recipients. Results Respondents generally practiced in an academic institution, incorporated the knowledge and skills learned during the short-term educational experience in their practices, and introduced the information acquired to medical students, residents, and colleagues alike. In general, the recipients demonstrated a substantial progress in their career development. Conclusion Our impression is that this short-term educational experience was successful in imparting new knowledge and skills to the scholarship recipients who then shared these experiences with their peers and trainees. Further study will be required to understand the impact of this program on the long-term professional development of the recipients and enhanced health care of the region.